Besser ohne Bargeld? Gesamtwirtschaftliche Wohlfahrtsverluste der Bargeldabschaffung - Gerhard Rösl; Franz Seitz; Karl-Heinz Tödter (Research On Money in the Economy (ROME), 2017)
– To broaden the operational scope of monetary policy, several authors suggest cash abolishment as an appropriate means of breaking through the zero lower bound. The key question in this respect is: What are the costs of such a proposal? We argue that the welfare costs of bypassing the zero lower bound can be dealt with analytically and empirically by assuming negative interest rates on cash holdings. Adopting a money-in-the-utility-function (MIU) model, we measure the welfare loss in terms of the amount needed to compensate consumers (compensated variation), and as excess burden (deadweight loss) imposed on the economy. Firstly, we gauge the welfare effects of abolishing cash, both, for the Euro area and for Germany, and we perform several robustness checks. Secondly, we broaden the analysis by taking into account the liquidity services of assets included in the monetary aggregates M1 and M3, and we contrast the results for the year 2015 with those for the pre-crisis period 2005. Our findings suggest that the welfare losses of negative interest rates incurred by consumers and society are large, notably if implemented in a low interest rate environment. Imposing a negative interest rate of 3 percent on cash holdings and reducing the interest on all assets included in M3 creates a deadweight loss of exteuro 62bn for euro area and of exteuro18bn for Germany. The annual compensation required by consumers in the euro area as well as in Germany is equivalent to 2.2 percent of GDP or about exteuro700 per capita. Thus, stepping into deep negative interest rates turns out to be a very costly economic experiment, leaving aside the potential risks and negative side effects of protracted and intensified unconventional monetary policy.
Keywords: E41; E21; E58; I3; 330; Zero lower bound; cash abolishment; negative interest rates; welfare loss; compensated variation; deadweight loss